Environment-friendly slurry dehydrating agent and preparation method thereof

By combining the flocculation, adsorption and water-regulating mechanisms of various raw materials, an environmentally friendly mud dehydration agent was developed, which solved the problem of unstable dehydration effect in the prior art, achieved efficient mud dehydration, and reduced treatment costs and Environmental impact.

CN119241031APending Publication Date: 2025-01-03SHANDONG LUQIAO CONSTR
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411394686.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

When used, the dehydration treatment effect of existing mud dehydrating agents is unstable, resulting in the water content of mud still above 80%, and the deep dehydration of the sludge cannot be achieved, affecting the treatment cost and environmental protection.

Method used

Develop an environmentally friendly mud dehydrating agent, including polysilicates, cationic polyacrylamide, modified lignin coagulant, sodium dodecylbenzene sulfonate, calcium oxide and polyaluminum chloride, through flocculation and adsorption , reduce water surface tension, adjust pH and other mechanisms to promote the aggregation and precipitation of sludge particles and improve dehydration efficiency.

Benefits of technology

It significantly improves the dehydration performance of the mud, reduces the moisture content of the mud, saves treatment and transportation costs, reduces the impact on the environment, and is suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005073425490000061
    Figure BDA0005073425490000061
  • Figure BDA0005073425490000071
    Figure BDA0005073425490000071
  • Figure BDA0005073425490000081
    Figure BDA0005073425490000081
Patent Text Reader

Abstract

The invention relates to the technical field of slurry treatment, and particularly discloses an environment-friendly slurry dehydrating agent and a preparation method thereof. The environment-friendly mud dehydrating agent is prepared from the following raw materials in parts by weight: 10 to 20 parts of polysilicate, 4 to 8 parts of cationic polyacrylamide, 5 to 10 parts of modified lignin coagulant, 4 to 10 parts of sodium dodecyl benzene sulfonate, 10 to 15 parts of calcium oxide, 15 to 20 parts of polyaluminum chloride and 8 to 12 parts of diatomite. The preparation method of the environment-friendly slurry dehydrating agent comprises the following steps: mixing the polysilicate, the cationic polyacrylamide, the modified lignin coagulant, the sodium dodecyl benzene sulfonate, the calcium oxide, the polyaluminum chloride and the diatomite according to the proportion, and drying at 80-90 DEG C for 40-60 minutes to obtain the environment-friendly slurry dehydrating agent. The mud dehydrating agent prepared by the invention is good in mud dehydrating performance, green and environment-friendly, and good in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of mud treatment, and in particular to an environmentally friendly mud dehydrating agent and a preparation method thereof. Background Art

[0002] As my country's understanding of environmental protection and ecological civilization construction continues to deepen, in order to solve the problem of waste mud treatment and disposal during construction, management departments have higher and higher requirements for waste mud treatment. In order to achieve the goal of waste mud reduction, resource utilization, and harmlessness, and protect the ecological environment, many provinces and cities in my country have issued relevant waste mud management regulations, and the disposal and management of waste mud has entered the track of legal management. Therefore, economic and environmentally friendly treatment of waste mud has become an urgent need for social development.

[0003] At present, the treatment of waste mud is mainly to transport the mud to the waste dump by tank trucks, but the mud has a large output and high water content, which is very unfavorable for treatment and transportation. Mud dehydration, as the most important pre-treatment process, is a very critical link to reduce the subsequent treatment and disposal costs of mud. Mud dehydration can greatly reduce the accumulation area of ​​mud, save transportation costs, and avoid the adverse effects of long-term storage of mud in the waste dump on surrounding water resources and construction environment.

[0004] However, the existing mud dehydrating agent has the problem of unstable dehydration effect when used. The water content of the mud after dehydration is still above 80%, which cannot promote the deep dehydration of the sludge. Summary of the invention

[0005] In order to solve at least one of the above technical problems, a mud dehydrating agent with good dehydration performance and environmental protection is developed. The present application provides an environmentally friendly mud dehydrating agent and a preparation method thereof.

[0006] On the one hand, the present application provides an environmentally friendly mud dehydrating agent, comprising the following raw materials in parts by weight: 10-20 parts of polysilicate, 4-8 parts of cationic polyacrylamide, 5-10 parts of modified lignin coagulant, 4-10 parts of sodium dodecylbenzene sulfonate, 10-15 parts of calcium oxide, 15-20 parts of polyaluminium chloride, and 8-12 parts of diatomaceous earth.

[0007] By adopting the above technical solution, the environmentally friendly mud dehydrating agent in this application combines the advantages of multiple raw materials and improves the mud dehydrating performance. Specifically, Polysilicate is used as a flocculant, which can promote the aggregation of sludge particles through electrical neutralization, adsorption bridging, etc., improve the sedimentation performance of sludge, and help the subsequent dehydration treatment; Cationic polyacrylamide is a highly efficient organic polymer flocculant with a strong flocculation effect. It can effectively compress the double electrical layer between sludge particles, enhance the mutual attraction between particles, form larger flocs, and facilitate dehydration. Modified lignin coagulant: After chemical modification, lignin has improved its coagulation ability in water treatment, can adsorb and flocculate fine suspended particles, and helps improve the dewatering performance of sludge; Sodium dodecylbenzene sulfonate can effectively reduce the surface tension of water, increase the wettability of sludge particles, help disperse and emulsify oil pollution, thereby improving the separation effect of sludge and increasing dehydration efficiency; Calcium oxide dissolves in water to form calcium hydroxide, which has a strong alkalinity and can adjust the pH value of sludge and promote the decomposition of organic matter. It can also play a certain coagulant role and promote the coagulation and precipitation of particles. Polyaluminium chloride promotes the coagulation of sludge particles and improves the settling rate and compression performance by compressing the double electrical layer and adsorbing and bridging. Diatomaceous earth is used as an auxiliary filter aid. Diatomaceous earth has a porous structure, which can increase the porosity of the sludge filter cake and improve the filtration efficiency. At the same time, it can also adsorb some organic matter and microorganisms, which helps to improve the quality of the filtrate.

[0008] Optionally, the preparation method of the modified lignin coagulant comprises the following steps: A1. Dissolve the dealkalized lignin in water, adjust the pH to neutral, and after the lignin is completely dissolved, heat the water bath to 65-70°C and stir continuously to obtain a lignin solution with a mass concentration of 0.05-0.08 g / mL; A2, adding a 4% by mass ammonium persulfate solution to the lignin solution obtained in step A1, and then adding acrylamide and methacryloyloxyethyl trimethyl ammonium chloride, stirring and reacting to obtain a mixed solution; A3. Add anhydrous ethanol to the mixed solution obtained in step A2, filter, wash and dry to obtain the modified lignin coagulant.

[0009] Through the above technical scheme, the present application selects acrylamide and methacryloyloxyethyltrimethylammonium chloride to graft and modify lignin, so that the prepared modified lignin coagulant has electrical neutralization properties, and the unique aromatic ring structure of lignin itself can not only play an aggregate supporting role, which is beneficial to improve the compressibility of the mud cake and enhance its mud cake permeability, but also the unique macromolecular structure of lignin also gives the modified lignin coagulant good bonding, bridging and flocculation effects, thereby further improving the dehydration performance of the mud dehydrator.

[0010] Optionally, in step A2, the volume ratio of the lignin solution to the ammonium sulfate solution is 8-10:1.

[0011] Optionally, the weight ratio of the lignin, acrylamide and methacryloyloxyethyltrimethylammonium chloride is 1:1-1.5:1.8-3.

[0012] Optionally, the weight ratio of the lignin, acrylamide and methacryloyloxyethyltrimethylammonium chloride is 1:1.3:2.5.

[0013] Optionally, the weight ratio of the polysilicate to the cationic polyacrylamide is 2-3:1.

[0014] Through the above technical scheme, when polysilicate and cationic polyacrylamide are used in combination, the dosage of both can be greatly reduced, which can not only save costs, but also avoid corrosion of pipelines caused by excessive addition of inorganic dehydrating agents. From the characteristics of the treated mud, polysilicate and cationic polyacrylamide both play an adsorption and bridging role in the process of conditioning the mud, but their skeleton support effect also makes the treated mud have better dehydration performance.

[0015] Optionally, the weight ratio of the polysilicate to the cationic polyacrylamide is 2.5:1.

[0016] Optionally, the polysilicate is selected from one of polysilicate iron, polysilicate aluminum iron and polysilicate aluminum iron magnesium.

[0017] Optionally, the cationic polyacrylamide is selected from one of CPAM9108, CPAM9110 and CPAM9112.

[0018] In a second aspect, the present application provides a method for preparing the above-mentioned environmentally friendly mud dehydrating agent, comprising the following steps: mixing polysilicate, cationic polyacrylamide, modified lignin coagulant, sodium dodecylbenzene sulfonate, calcium oxide, polyaluminum chloride and diatomaceous earth according to a proportion, and drying at 80-90°C for 40-60 minutes to obtain the environmentally friendly mud dehydrating agent.

[0019] By adopting the above technical scheme, the preparation method of the mud dehydrating agent of the present application is simple, and the prepared dehydrating agent has high-efficiency dehydrating performance and is suitable for industrial promotion.

[0020] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The environmentally friendly mud dewatering agent in this application combines the advantages of multiple raw materials to achieve the improvement of mud dewatering performance. Specifically, polysilicate is used as a flocculant, which can promote the aggregation of sludge particles through electrical neutralization, adsorption bridging and other methods, improve the sedimentation performance of sludge, and help the subsequent dewatering treatment; cationic polyacrylamide is a highly efficient organic polymer flocculant with a strong flocculation effect. It can effectively compress the double electrical layer between sludge particles, enhance the mutual attraction between particles, and form larger flocs for easy dehydration; modified lignin coagulant, after chemical modification, the lignin has improved its coagulation ability in water treatment, can adsorb and flocculate fine suspended particles, and help improve the dewatering performance of sludge; sodium dodecylbenzene sulfonate can effectively reduce the surface tension of water, Increasing the wettability of sludge particles helps to disperse and emulsify oil, thereby improving the separation effect of sludge and increasing dehydration efficiency; calcium oxide dissolves in water to form calcium hydroxide, which has a strong alkalinity and can adjust the pH value of sludge and promote the decomposition of organic matter. It can also play a certain coagulant role and promote the coagulation and precipitation of particles; polyaluminium chloride promotes the coagulation of sludge particles by compressing the double electrical layer and adsorbing and bridging, thereby increasing the sedimentation rate and compression performance; diatomaceous earth is used as an auxiliary filter aid. Diatomaceous earth has a porous structure and can increase the porosity of the sludge filter cake and improve the filtration efficiency. At the same time, it can also adsorb some organic matter and microorganisms, which helps to improve the quality of the filtrate.

[0021] 2. The preparation method of the mud dehydrating agent of the present application is simple, and the prepared dehydrating agent has high-efficiency dehydrating performance and is suitable for industrial promotion. DETAILED DESCRIPTION

[0022] The present application is further described in detail below with reference to the embodiments.

[0023] The present application designs an environmentally friendly mud dehydrating agent, which includes the following raw materials in parts by weight: 10-20 parts of polysilicate, 4-8 parts of cationic polyacrylamide, 5-10 parts of modified lignin coagulant, 4-10 parts of sodium dodecylbenzene sulfonate, 10-15 parts of calcium oxide, 15-20 parts of polyaluminium chloride and 8-12 parts of diatomaceous earth.

[0024] An environmentally friendly mud dehydrating agent of the present application is prepared by the following method, comprising the following steps: polysilicate, cationic polyacrylamide, modified lignin coagulant, sodium dodecylbenzene sulfonate, calcium oxide, polyaluminum chloride and diatomaceous earth are mixed according to a proportion, and dried at 80-90°C for 40-60 minutes to obtain the environmentally friendly mud dehydrating agent.

[0025] The environmentally friendly mud dehydrating agent of the present application can be used in the field of mud treatment technology. Specific embodiments

[0026] Preparation Example 1-3 Preparation Example 1 This preparation example provides a modified lignin coagulant, and the preparation method comprises the following steps: A1. Dissolve the dealkalized lignin in water, adjust the pH to neutral, and after the lignin is completely dissolved, heat the water bath to 65°C and stir continuously to obtain a lignin solution with a mass concentration of 0.08 kg / L. A2, adding a 4% by mass ammonium persulfate solution to the lignin solution obtained in step A1, and then adding acrylamide and methacryloyloxyethyl trimethyl ammonium chloride, stirring and reacting to obtain a mixed solution; A3, adding anhydrous ethanol to the mixed solution obtained in step A2, filtering, washing and drying to obtain the modified lignin coagulant; The weight ratio of lignin, acrylamide and methacryloyloxyethyltrimethylammonium chloride is 1:1:1.8; In step A2, the volume ratio of the lignin solution to the ammonium sulfate solution is 8:1.

[0027] Preparation Example 2 This preparation example provides a modified lignin coagulant, and the preparation method comprises the following steps: A1. Dissolve the dealkalized lignin in water, adjust the pH to neutral, and after the lignin is completely dissolved, heat the water bath to 68°C and stir continuously to obtain a lignin solution with a mass concentration of 0.06 kg / L. A2, adding a 4% by mass ammonium persulfate solution to the lignin solution obtained in step A1, and then adding acrylamide and methacryloyloxyethyl trimethyl ammonium chloride, stirring and reacting to obtain a mixed solution; A3, adding anhydrous ethanol to the mixed solution obtained in step A2, filtering, washing and drying to obtain the modified lignin coagulant; The weight ratio of lignin, acrylamide and methacryloyloxyethyl trimethyl ammonium chloride is 1:1.3:2.5; In step A2, the volume ratio of the lignin solution to the ammonium sulfate solution is 9:1.

[0028] Preparation Example 3 This preparation example provides a modified lignin coagulant, and the preparation method comprises the following steps: A1. Dissolve the dealkalized lignin in water, adjust the pH to neutral, and after the lignin is completely dissolved, heat it in a water bath to 70°C and stir continuously to obtain a lignin solution with a mass concentration of 0.05 kg / L. A2, adding a 4% by mass ammonium persulfate solution to the lignin solution obtained in step A1, and then adding acrylamide and methacryloyloxyethyl trimethyl ammonium chloride, stirring and reacting to obtain a mixed solution; A3, adding anhydrous ethanol to the mixed solution obtained in step A2, filtering, washing and drying to obtain the modified lignin coagulant; The weight ratio of lignin, acrylamide and methacryloyloxyethyl trimethyl ammonium chloride is 1:1.5:3; In step A2, the volume ratio of the lignin solution to the ammonium sulfate solution is 10:1.

[0029] Example 1 This embodiment provides an environmentally friendly mud dehydrating agent, which includes the following raw materials by weight: 12 parts of polysilicate, 6 parts of cationic polyacrylamide, 5 parts of modified lignin coagulant, 4 parts of sodium dodecylbenzene sulfonate, 10 parts of calcium oxide, 15 parts of polyaluminium chloride, and 8 parts of diatomaceous earth; Wherein, the polysilicate is selected from polymerized ferric silicate, and the cationic polyacrylamide is selected from CPAM9112.

[0030] The preparation method of the environmentally friendly mud dehydrating agent in this preparation example includes the following steps: mixing polysilicate, cationic polyacrylamide, modified lignin coagulant, sodium dodecylbenzene sulfonate, calcium oxide, polyaluminum chloride and diatomaceous earth according to a proportion, and drying at 85°C for 50 minutes to obtain the environmentally friendly mud dehydrating agent.

[0031] Embodiment 2-4 Example 2 The difference between this embodiment and embodiment 1 is that, when preparing the environmentally friendly mud dehydrating agent, the total weight of the polysilicate and the cationic polyacrylamide is 18 parts, and the weight ratio of the polysilicate to the cationic polyacrylamide is 2.3:1.

[0032] Example 3 The difference between this embodiment and embodiment 1 is that, when preparing the environmentally friendly mud dehydrating agent, the total weight of the polysilicate and the cationic polyacrylamide is 18 parts, and the weight ratio of the polysilicate to the cationic polyacrylamide is 2.5:1.

[0033] Example 4 The difference between this embodiment and embodiment 1 is that, when preparing the environmentally friendly mud dehydrating agent, the total weight of the polysilicate and the cationic polyacrylamide is 18 parts, and the weight ratio of the polysilicate to the cationic polyacrylamide is 3:1.

[0034] Comparative Examples 1-3 Comparative Example 1 The difference between this comparative example and Example 3 is that no polysilicate is added when preparing the environmentally friendly mud dehydrating agent.

[0035] Comparative Example 2 The difference between this comparative example and Example 3 is that cationic polyacrylamide is not added when preparing the environmentally friendly mud dehydrating agent.

[0036] Comparative Example 3 The difference between this comparative example and Example 3 is that no modified lignin coagulant is added in the environmentally friendly mud dehydrating agent.

[0037] Experimental testing The mud was homogenized and stirred, and the water content was adjusted to 94%. The mud dehydrating agent was added into the mud at a dosage of 3.0 g / g dry mud. The mud was stirred for 3 hours, and then transported to the plate and frame filter press by a mud pump for mechanical filtration and dehydration. The water content of the mud after dehydration was calculated as follows: Mud water content (%) = (m-m1) ÷ m × 100%; Where m is the mass of the mud sample after dehydration; m1 is the mass of the mud sample after drying the mud sample at 105°C to constant weight.

[0038] The experimental test results of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.

[0039] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-3 Result analysis: The difference between Examples 2-4 and Example 1 is that, when preparing the environmentally friendly mud dewatering agent, the total weight of polysilicate and cationic polyacrylamide is 18 parts, and the weight ratio of polysilicate and cationic polyacrylamide is different. Combined with the experimental test results in Table 1, it can be seen that when the weight ratio of polysilicate and cationic polyacrylamide is 2.5:1, the dehydration performance of the prepared environmentally friendly mud dewatering agent is better. The difference between Comparative Example 1 and Example 3 is that, when preparing the environmentally friendly mud dewatering agent, cationic polyacrylamide is not added. The difference between Comparative Example 2 and Example 3 is that, when preparing the environmentally friendly mud dewatering agent, polysilicate is not added. The difference between Comparative Example 3 and Example 3 is that, when preparing the environmentally friendly mud dewatering agent, modified lignin coagulant is not added. Combined with the experimental test results in Table 1, it can be seen that when preparing an environmentally friendly mud dewatering agent, the compound use of polysilicate and cationic polyacrylamide can better improve the comprehensive performance of the prepared environmentally friendly mud dewatering agent, and the modified lignin coagulant can effectively improve the dehydration performance of the mud dewatering agent.

[0040] Embodiment 5-6 The difference between Example 5-6 and Example 3 is that the weight fractions of some components are changed when preparing the environmentally friendly mud dehydrating agent. See Table 2 for the difference.

[0041] Table 2 - Differences between Examples 5-6 and Example 3 Ingredients (parts by weight) Example 3 Example 5 Example 6 Polysilicate 12.9 12.9 12.9 Cationic polyacrylamide 5.1 5.1 5.1 Modified lignin coagulant 5 8 10 Sodium dodecylbenzenesulfonate 4 6 10 Calcium Oxide 10 13 15 Polyaluminium chloride 15 17 15 diatomite 8 10 12 The experimental test results of Examples 5-6 are shown in Table 3.

[0042] Table 3 - Experimental test results of Examples 5-6 Result analysis: The difference between Example 5-6 and Example 3 is that when preparing the environmentally friendly mud dehydrating agent, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that when preparing the environmentally friendly mud dehydrating agent, the environmentally friendly mud dehydrating agent prepared in Example 5 has better dehydration performance.

[0043] Embodiment 7-8 Example 7 The difference between this embodiment and embodiment 5 is that when preparing the environmentally friendly mud dehydrating agent, the preparation parameters of the modified lignin coagulant used are different. The modified lignin coagulant in this embodiment is prepared by Preparation Example 2.

[0044] Example 8 The difference between this embodiment and embodiment 5 is that when preparing the environmentally friendly mud dehydrating agent, the preparation parameters of the modified lignin coagulant used are different. The modified lignin coagulant in this embodiment is prepared by Preparation Example 3.

[0045] The experimental test results of Examples 7-8 are shown in Table 4.

[0046] Table 4 - Experimental test results of Examples 7-8 Result analysis: The difference between Example 7-8 and Example 5 is that, when preparing an environmentally friendly mud dehydrating agent, the modified lignin coagulant prepared in Preparation Example 2 can better improve the dehydration performance of the mud dehydrating agent.

[0047] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An environmentally friendly mud dehydrating agent, characterized in that: The invention comprises the following raw materials in parts by weight: 10-20 parts of polysilicate, 4-8 parts of cationic polyacrylamide, 5-10 parts of modified lignin coagulant, 4-10 parts of sodium dodecylbenzene sulfonate, 10-15 parts of calcium oxide, 15-20 parts of polyaluminium chloride and 8-12 parts of diatomaceous earth.

2. The environmentally friendly mud dehydrating agent according to claim 1, characterized in that: The preparation method of the modified lignin coagulant comprises the following steps: A1. Dissolve the dealkalized lignin in water, adjust the pH to neutral, and after the lignin is completely dissolved, heat the water bath to 65-70°C and stir continuously to obtain a lignin solution with a mass concentration of 0.05-0.08 g / mL; A2, adding a 4% by mass ammonium persulfate solution to the lignin solution obtained in step A1, and then adding acrylamide and methacryloyloxyethyl trimethyl ammonium chloride to react with stirring to obtain a mixed solution; A3. Add anhydrous ethanol to the mixed solution obtained in step A2, filter, wash and dry to obtain the modified lignin coagulant.

3. The environmentally friendly mud dehydrating agent according to claim 2, characterized in that: In step A2, the volume ratio of the lignin solution to the ammonium sulfate solution is 8-10:

1.

4. The environmentally friendly mud dehydrating agent according to claim 2, characterized in that: The weight ratio of the lignin, acrylamide and methacryloyloxyethyl trimethyl ammonium chloride is 1:1-1.5:1.8-3.

5. The environmentally friendly mud dehydrating agent according to claim 4, characterized in that: The weight ratio of the lignin, acrylamide and methacryloyloxyethyltrimethylammonium chloride is 1:1.3:2.

5.

6. The environmentally friendly mud dehydrating agent according to claim 1, characterized in that: The weight ratio of the polysilicate to the cationic polyacrylamide is 2-3:

1.

7. The environmentally friendly mud dehydrating agent according to claim 6, characterized in that: The weight ratio of the polysilicate to the cationic polyacrylamide is 2.5:

1.

8. The environmentally friendly mud dehydrating agent according to claim 1, characterized in that: The polysilicate is selected from one of polysilicate iron, polysilicate aluminum iron and polysilicate aluminum iron magnesium.

9. The environmentally friendly mud dehydrating agent according to claim 1, characterized in that: The cationic polyacrylamide is selected from one of CPAM9108, CPAM9110 and CPAM9112.

10. A method for preparing the environmentally friendly mud dehydrating agent according to any one of claims 1 to 9, characterized in that: The following steps are involved: The environmentally friendly mud dehydrating agent is prepared by mixing polysilicate, cationic polyacrylamide, modified lignin coagulant, sodium dodecylbenzene sulfonate, calcium oxide, polyaluminium chloride and diatomaceous earth according to a proportion, and drying at 80-90° C. for 40-60 minutes.

Citation Information

Patent Citations

  • Organic compound sewage dehydrating conditioning agent prepared from paper mill sludge and preparation method

    CN106946438A

  • Hyperbranched lignin-grafted cationic polyacrylamide flocculating agent and preparation method thereof

    CN109280174A

  • Efficient multifunctional sludge dewatering treatment agent, composite preparation method and application method thereof

    CN116062969A

  • Organic sludge dehydrating agent

    CN118439776A

  • Sludge dehydrating agent

    JP1988252600A